Perlindungan Hak Cipta Film Terhadap Konten Spoiler di YouTube - Sipahutar, Mulia Risky; Akyuwen, Rory Jeff; Sopamena, Ronald Fadly (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Nowadays, the use of social media is often used as a forum for channeling a creative work. One of the media that is widely used is YouTube. This is because youtube provides economic benefits to creators who want to participate in sharing their copyrighted works. With the development of social media and the ease of sharing the copyrighted work gave rise to many forms of copyright infringement circulating on YouTube.Purposes of the Research:  The purpose of this study is to know and understand copyright infringement committed by spoiler creator content on Youtube and legal protection for movie creators from spoiler content on YouTube.Methods of the Research: The research method used is normative juridical, the problem approach used in the research is a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials carried out in this study with library research, then analyzed using qualitative methods.research Results of the Research: Based on research, currently the act of copyright infringement of spoiler creators' movies is rampant on YouTube. This action arises due to several factors, including low law enforcement against content that violates copyright, and the rapid development of information technology so that there is always a gap to spread content that violates copyright. The solution to copyright infringement is to close access or block content and active socialization from the government and social society regarding the importance of respecting and appreciating every copyrighted work that exists.